Lektur Klasik Kependidikan Islam Genre Psikologi: Classic Lecture On Islamic Education Psychology Genre - Cibro, Andika; Mukti, Abd.; Arsyad, Junaidi (FITRAH: International Islamic Education Journal, 2024)
This study aims to explore classical Islamic educational literature within the field of psychology, to be used as a comparative framework or to identify its relevance in the modern era. The research employs a qualitative descriptive approach through library research methods. The findings indicate that psychology has a significant impact on the process of education and learning. Ibn Miskawayh, At-Tabari, and Fakhruddin Ar-Razi are notable classical Islamic figures whose works continue to be studied and developed to this day. Their contributions to psychology hold potential for application in various societal contexts and conditions. The psychological insights of Ibn Miskawayh, At-Tabari, and Fakhruddin Ar-Razi remain relevant and applicable to contemporary Islamic education.   Abstrak Penelitian ini bertujuan untuk membahas lektur klasik kependidikan islam pada genre psikologi untuk dapat dijadikan perbandingan atau bahkan ditemukan relevansi pada era modern. Penelitian ini merupakan penelitian kepustakaan (libraryresearch) dengan menggunakan pendekatan kualitatif deskriptif. Hasil kajian menjelaskan Psikologi memiliki pengaruh besar dalam proses pendidikan dan pembelajaran. Ibn Miskawayh, At-Tabari dan Fakhruddin Ar-Razi merupakan tokoh islam klasik yang populer dikaji dan dikembangkkan hingga saat ini, ketiganya memiliki karya-karya pada aspek psikologi yang berpotensi dalam sejumlah upaya aktivitas yang dilalui masyarakat di berbagai situasi dan kondisi. Pada kependidikan islam pemikiran Ibn Miskawayh, At-Tabari dan Fakhruddin Ar-Razi tentang psikologi masih relevan untuk diterapkan dimasa sekarang.